2014
DOI: 10.1002/asjc.1019
|View full text |Cite
|
Sign up to set email alerts
|

Robust Disturbance Attenuation in Hamiltonian Systems Via Direct Digital Control

Abstract: The discrete‐time robust disturbance attenuation problem for the n‐degrees of freedom (dof) mechanical systems with uncertain energy function is considered in this paper. First, it is shown in the continuous time‐setting that the robust control problem of n‐dof mechanical systems can be reduced to a disturbance attenuation problem when a specific type of control rule is used. Afterwards, the robust disturbance attenuation problem is formulised as a special disturbance attenuation problem. Then, the discrete‐ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In this section the main results of our previous studies [20,21] are summarized to exploit them in the sequel while obtaining the new results. In [20,21], it has been shown that a static feedback of the form…”
Section: Previous Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this section the main results of our previous studies [20,21] are summarized to exploit them in the sequel while obtaining the new results. In [20,21], it has been shown that a static feedback of the form…”
Section: Previous Resultsmentioning
confidence: 99%
“…In [21] it has been shown that the robust control problem for n-dof mechanical systems can be reduced to a disturbance attenuation problem. The port-controlled Hamiltonian formulation of the considered class of uncertain systems is …”
Section: Robust Disturbance Attenuationmentioning
confidence: 99%
See 2 more Smart Citations
“…It might be noted that the discrete time models proposed here were used in the sampled-data control of port-Hamiltonian systems in the sense of passivity-based control and disturbance attenuation in [14][15][16][17][18], respectively. It should be emphasized that [17] reported a real application where the proposed model was easily and successfully utilized.…”
Section: Introductionmentioning
confidence: 99%